THE RELEVANCE OF THE PRESIDENTIAL THRESHOLD IN THE SIMULTANEOUS PRESIDENTIAL ELECTION (PILPRES) IN 2024 - Ananda, Narullah Rizky (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The 2024 Simultaneous Presidential Election (Pilpres) will be one of the most interesting elections in Indonesia in history. In the 2024 Simultaneous Presidential Election, the Presidential Threshold will be a key factor influencing the results of the Presidential Election. The Presidential Nomination Threshold is the number of votes required by a candidate to be able to nominate for President. In this regard, there needs to be research on the urgency of using the 20% threshold in Presidential nominations in the 2024 simultaneous presidential elections. Setting the Presidential Threshold system in Indonesia. And the relevance of the Presidential Threshold in Indonesia with a multiparty system. This type of research uses normative legal research. Research legal materials are collected by inventorying and classifying then analyzed qualitatively and presented in descriptive form. The approach used is the Presidential Threshold legislative approach which is closely related to simultaneous elections, the Presidential Threshold can determine the final results of a presidential election. The Presidential Threshold also determines the alignment that will occur between the legislative and executive institutions. Taking the threshold as a condition for nominating the President is considered irrelevant because it uses the vote share of the previous five years which does not necessarily have the same electability in the following year.